PROMOTION OF HISTORIC CITIES THROUGH DIGITAL PLATFORMS AND ANALYSIS OF ITS IMPACT ON THE REGIONAL ECONOMY - Rozikulov, Ahmadjon Abdurashidovich (THE INNOVATION ECONOMY, 2026)
This article examines the role of digital platforms in promoting historical cities and their impact on regional economic growth. The study, conducted in the case of Termez, uses a mixed-methods approach to analyze the impact of websites, mobile applications, and virtual tours on tourist arrivals, local business income, and job creation.